REVITALIZING HISTORICAL TOURISM DESTINATION THROUGH GAMIFICATION AND STORYTELLING: A CASE STUDY OF THE WARUNGBOTO SITE IN YOGYAKARTA - Bonifasia Yuniar Rifani; Asti Ayuningsih (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2025)
AbstractThis study examines the potential development of gamification and storytelling in revitalizing historical tourism destinations at the Warungboto Site, Yogyakarta. The research aims to develop a concept for historical site development by integrating digital technology and gaming elements to enhance tourist experiences. Through analyzing the site's strengths in natural, historical, and spiritual aspects, the